2021
DOI: 10.3389/fphys.2021.690185
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Provide Insights Into Function and Evolution of Odorant Binding Proteins in Cydia pomonella

Abstract: Insect olfaction is vital for foraging, mating, host-seeking, and avoidance of predators/pathogens. In insects, odorant binding proteins (OBPs) are involved in transporting hydrophobic odor molecules from the external environment to receptor neurons. The codling moth, Cydia pomonella, one of the most destructive insect fruit pests, causes enormous economic losses. However, little is known about the number, variety, gains and losses, and evolution of OBP genes in C. pomonella. Here we report the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
(122 reference statements)
1
3
0
Order By: Relevance
“…In contrast, HcunGOBP1 showed a weak binding affinity, but was consistent (or significant) to all four sex pheromone components (Figs 4 and 5, and Table 1). Similar to previous studies on B. mori , 53 Conopomorpha sinensis , 54 C. pomonella , 55 G. molesta , 56 Heliothis virescens , 57 P. xylostella , 58 and S. littoralis , 59 our results also support the hypothesis that GOBPs might function as an additional selectivity level and may contribute to pheromone discrimination. We suggested that the differential binding affinity in the sex pheromone components might be due to alcohol oxidase which is involved in converting fatty alcohols to pheromone aldehyde analogs 60,61 .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, HcunGOBP1 showed a weak binding affinity, but was consistent (or significant) to all four sex pheromone components (Figs 4 and 5, and Table 1). Similar to previous studies on B. mori , 53 Conopomorpha sinensis , 54 C. pomonella , 55 G. molesta , 56 Heliothis virescens , 57 P. xylostella , 58 and S. littoralis , 59 our results also support the hypothesis that GOBPs might function as an additional selectivity level and may contribute to pheromone discrimination. We suggested that the differential binding affinity in the sex pheromone components might be due to alcohol oxidase which is involved in converting fatty alcohols to pheromone aldehyde analogs 60,61 .…”
Section: Discussionsupporting
confidence: 91%
“…The general odorant-binding proteins have critical functions in the recognition of host plants and mates in lepidopteran insects [15,28]. In previous studies, a total of four general odorant-binding protein genes were characterized in C. pomonella, including one GOBP1 and three duplicates of the GOBP2 gene [24,25]. The three GOBP2 genes were named CpomGOBP2a, CpomGOBP2b, and CpomGOBP2c.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that the copies of CpomOR3 enhanced the capabilities of mate location and host plant recognition. Using genome and transcriptome analysis, scientists determined that the CpomGOBP2 genes have been duplicated twice, named CpomGOBP2a, CpomGOBP2b, and CpomGOBP2c [24,25]. However, the functions of these three CpomGOBP2 genes remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, this number was significantly greater than that of CXE genes identified in other species reported, such as C. pomonella (12) ( Huang et al, 2016 ), C. suppressalis (19) ( Liu et al, 2015a ), H. parallela (20) ( Yi et al, 2021 ), and A. lepigone (20) ( Zhang et al, 2017c ). The difference in gene numbers among different species might depend on the evolution of divergent behaviors in the long term, which resulted in gene duplication and loss ( Zhang et al, 2017b ; Huang et al, 2021 ). In addition, the sample preparation and sequencing method/depth might also be a reason.…”
Section: Discussionmentioning
confidence: 99%